Innovation management : systemic framework and China's exploration - Chen, Jin; Zheng, Gang (McGraw-Hill Education, 2019)
The key for lasting competitive advantage lies in embracing innovation as a core value and managing it effectively. Innovation Management provides a comprehensive overview of innovation theory and a framework for implementation, intended for business school students of Innovation Management, managers, and practitioners alike. In this new text, authors Jin Chen and Gang Zheng examine innovation from the perspectives of strategy, internal processes, resource management, and organizational culture. Numerous case studies, illustrating both successes and failures in innovation, include Tesla, P&G, Apple, Uber, Google, NVIDIA, Haier Group, Motorola, and Nokia. Staring from a systematic introduction to the types, process and models of innovation, the authors present a strategical management framework that includes models for indigenous innovation, total innovation, open innovation and holistic innovation. They outline the key roles played by management of capital, information and knowledge systems, human resources, and IP rights. Organizational systems that are designed to stimulate innovation within the corporation are detailed, and finally the authors examine the future of innovation management, focusing the need for sustainable innovation that recognized the importance of environmental and ecological concerns.